Taxonomy and biology of Simulium clarkei Stone & Snoddy (Diptera: Simuliidae), a poorly known black fly of the southeastern United States - Moulton, John K.; Adler, Peter H. (Zenodo, 2002)
Moulton, John K., Adler, Peter H. (2002): Taxonomy and biology of Simulium clarkei Stone & Snoddy (Diptera: Simuliidae), a poorly known black fly of the southeastern United States. Zootaxa 31: 1-7 : {"references": ["Adler, P. H. & Currie, D. C. (1986) Taxonomic resolution of three new species near Simulium vernum Macquart (Diptera: Simuliidae). Canadian Entomologist, 118, 1207-1220.", "Adler, P. H., Malmqvist, B. & Zhang, Y. (1999) Black flies (Diptera: Simuliidae) of northern Sweden: taxonomy, chromosomes, and bionomics. Entomologica Scandinavica, 29, 361-382.", "Crosskey, R. W. & Howard, T. M. (1997) A new taxonomic and geographical inventory of world blackflies (Diptera: Simuliidae). The Natural History Museum, London.", "Currie, D. C. (1986) An annotated list of and keys to the immature black flies of Alberta (Diptera: Simuliidae). Memoirs of the Entomological Society of Canada, 134, 1-90.", "Davies, D. M., Peterson, B. V., & Wood, D. M. (1962) The black flies (Diptera: Simuliidae) of Ontario. Part I. Adult identification and distribution with descriptions of six new species. Proceedings of the Entomological Society of Ontario, 92, 70-154.", "Golini, V. I. & Rothfels, K. (1984) The polytene chromosomes of North American blackflies in the Eusimulium canonicolum group (Diptera: Simuliidae). Canadian Journal of Zoology, 62, 2097-2109.", "Lowther, J. K. & Wood, D. M. (1964) Specificity of a black fly, Simulium euryadminiculum Davies, toward its host, the common loon. Canadian Entomologist, 96, 911-913.", "Peterson, B. V. (1981) Simuliidae. In: McAlpine, J. F., Peterson, B. V., Shewell, G. E., Teskey, H. J., Vockeroth, J. R., & Wood, D. M. (Eds.). Manual of Nearctic Diptera. Volume 1. Monograph No. 27. Research Branch, Agriculture Canada, Ottawa. Pp. 355-391.", "Rothfels, K. H. & Dunbar, R. W. (1953) The salivary gland chromosomes of the black fly Simulium vittatum Zett. Canadian Journal of Zoology, 31, 226-241.", "Smith, R. N., Cain, S. L., Anderson, S. H., Dunk, J. R., & Williams, E. S. (1998) Blackfly induced mortality of nestling red-tailed hawks. Auk, 115, 368-375.", "Stone, A. & Snoddy, E. L. (1969) The black flies of Alabama (Diptera: Simuliidae). Auburn University Agricultural Experiment Station Bulletin, 390, 1-93."]}